Dynamic parametric design and feasibility assessment for a high resistance measuring system. (October 2016) - Huang, Chien-Yi; Ying, Kuo-Ching
Highlights: A high resistance measuring system is used to monitor the current leakage. We construct a dynamic parameter design to optimize the test parameters. Test time, test voltage, charge time and pause interval are under consideration. GR&R results confirm that our suggested test parameters exhibit small variability. Abstract: A high resistance measuring system (HRMS) is used to measure the surface insulation resistance (SIR) values of the printed circuit board (PCB), and monitor whether a momentary circuit short and/or the case of current slow leakage occur, which will affect the electrical properties of electronic components. This study constructs a dynamic parameter design for optimization of the test parameters of the HRMS in order to obtain robust test results. The optimal test parameters for SIR testing are: 390 ms test time, 100 V test voltage, 100 V, 15 s charge time, and 100 s pause interval. Further investigation is conducted on the impact of the test parameters on the measurement performance.